CRISPR genome editing using computational approaches: A survey - Alipanahi, Roghayyeh; Safari, Leila; Khanteymoori, Alireza (Frontiers in Bioinformatics, 2023)
CRISPR-based gene editing has been widely used in various cell types and organisms. To make genome editing with CRISPR far more precise and practical, we must concentrate on the design of optimal gRNA and the selection of appropriate Cas enzymes. Numerous computational tools have been created in recent years to help researchers design the best gRNA for CRISPR researches. There are two approaches for designing an appropriate gRNA sequence (which targets our desired sites with high precision): experimental and predicting-based approaches. It's essential to reduce off-target sites when designing an optimal gRNA. Here we review both traditional and machine learning-based approaches for designing an appropriate gRNA sequence and predicting off-target sites. In this review, we summarize the key characteristics of all available tools (as far as possible) and compare them together. Machine learning-based tools and web servers are believed to become the most effective and reliable methods for predicting on-target and off-target activities of CRISPR in the future. However, these predictions are not so precise now and the performance of these algorithms -especially deep learning one’s- depends on the amount of data used during training phase. So, as more features are discovered and incorporated into these models, predictions become more in line with experimental observations. We must concentrate on the creation of ideal gRNA and the choice of suitable Cas enzymes in order to make genome editing with CRISPR far more accurate and feasible.